2019
DOI: 10.1001/jama.2019.4981
|View full text |Cite
|
Sign up to set email alerts
|

Management of Preexisting Diabetes in Pregnancy

Abstract: Importance: The presence of preexisting type 1 or type 2 diabetes in pregnancy increases the risk of adverse maternal and neonatal outcomes, such as preeclampsia, caesarian section, pre-term delivery, macrosomia and congenital defects. Approximately 0.9% of the 4,000,000 births in the United States are complicated by preexisting diabetes. Observations: Women with diabetes have increased risk for adverse maternal and neonatal outcomes and similar risks are present for either type 1 or type 2 diabetes. Both fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
74
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 92 publications
0
74
0
2
Order By: Relevance
“…With the aging of the population, urbanization, and related dramatic changes toward sedentary lifestyle during the past few decades, the prevalence of diabetes mellitus (DM) has been growing rapidly worldwide [1][2][3]. The number of people aged 18 years or older with DM globally is projected to rise from 451 million in 2017 to 693 million in 2045 [4].…”
Section: Introductionmentioning
confidence: 99%
“…With the aging of the population, urbanization, and related dramatic changes toward sedentary lifestyle during the past few decades, the prevalence of diabetes mellitus (DM) has been growing rapidly worldwide [1][2][3]. The number of people aged 18 years or older with DM globally is projected to rise from 451 million in 2017 to 693 million in 2045 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Among women with T2DM, the frequency of T2DM + HDP was similar between women with and without diabetic nephropathy (33.3% versus 11.3%); furthermore, the frequencies of women with T2DM + HDP or CH were similar (50.0% versus 28.9%). A recent review determined that it is also critical to screen for and manage retinopathy and nephropathy, and blood pressure goals must be considered carefully because lower treatment thresholds may be required for women with nephropathy [2].…”
Section: Discussionmentioning
confidence: 99%
“…The target HbA1c levels are <6.5% at conception and <6.0% during pregnancy. During pregnancy, continuous glucose monitoring can improve glycemic control and neonatal outcomes in women with T1DM [2]. Another review of pregnant women with T1DM indicated that the goals of preconception care are tight glycemic control with an HbA1c level of <7.0% and as close to 6.0% as possible, and the target HbA1c level during pregnancy is <6.0%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations